FACTORS AFFECTING AUDIT QUALITY (Empirical Study of Public Accounting Firms in the City of Surakarta and Yogyakarta) - Crismonika Anggun Kusuma Dewi; Suhendro; Purnama Siddi (Journal of Business, Management, & Accounting, 2020)
This study aims to analyze and test the effect of auditor experience, auditor accountability, independence, and auditor competence on audit quality. In this study, researchers conducted surveys at the Public Accounting Firm in the City of Surakarta and Yogyakarta. The population in this study were auditors working in public accounting firms in the cities of Surakarta and Yogyakarta. Purposive sampling is a method used in this study. The sample used in this study consisted of 32 auditors from 7 public accounting firms. Data used in this study were collected through a questionnaire method. By using the classic assumption test, and hypothesis testing using multiple linear regression test, t test and F test. The benefits of this study are to increase knowledge and references for readers or subsequent researchers regarding the effect of auditor experience, auditor accountability, auditor independence, and auditor competence on audit quality. The results of this study indicate that auditor independence and auditor competence significantly influence audit quality while auditor experience and auditor accountability have no significant effect on audit quality.